Perception of the Night Scene, An Analytical Study of the Visual Axis Characteristics in the old city canter of Sulaimani - Faraj, Raz Said (Sulaimani Journal for Engineering Sciences, 2019)
The perception of individuals to the urban scenes at night is different from that of the day. The previous studies dealt with the subject of the night scene in terms of the effect of artificial lighting in the formation of the night scene and its ability to increase the quality and aesthetics of the scene that designed for night use, but this research deals with other factors. The research problem show itself as: There is a difference in the perception of the viewer at night during the day, where some scenes attract people at night while not attracted by the day and vice versa, while other scenes attract individuals day and night. regardless of the type and efficiency of the lighting used. And the aim of the research, is to study the impact of those characteristics at night where as the people perception differs in the night. The research assumed: the perception of night scene changes according to that visual axes, and the most influential factor in this change is the attraction that result from the presence of a land mark in the axis of motion that changes the characteristics of the visual axis between night and day. And between nightscape and another. The importance of research: is to determine the characteristics that make the scene acceptable to individuals through day and night, and limit some recommendations to hire those characteristics in order to increase the vitality of the urban environment and increase the efficiency of use. In order to achieve this, the research based on a methodology consist of a theoretical base include the explanation of concepts like (urban scene, night scene, visual perception, visual axis) in order to achieve this the research adapt the semantic measurement to measure the people perception of the scene, during the night and day periods of the same scenes, and then compare the results to analyze the differences between them and explore the reasons behind it. Research has found that the characteristics of the axis differ in terms of their impact on the people attraction, as the emergence of the landmarks at the end of the visual axis is the most influential attraction element to people at night. In the night scene people need to see the land marks in compared to the other elements to be able to complete their journey. And that people do not care about the start points as the end points in the journey, in the night compared to the daytime. Keywords: night scene, visual axis, urban landmarks.
Keywords: Night scene; Visual axis; urban land marks; Sulaimani centre; Mawlawi Street